A case report on leucine rich glioma inactivated 1 antibody encephalitis - Agarwal, Vikas; Gongati, Nissi; Kachu, Ravi (International Journal of Research in Medical Sciences, 2024)
Anti-leucine rich glioma inactivated 1 (LGI1) antibody-mediated encephalitis represents an autoantibody mediated variant of limbic encephalitis (LE). We hereby report the case of a 69-year-old female patient experiencing symptoms of giddiness and forgetfulness, which have persisted for the past 90 days. Additionally, she has exhibited behaviours such as irrelevant conversations, confusion, and jerky movements. Upon reviewing her medical history, it was found that she has been diagnosed with hypertension and bronchial asthma, both of which are being managed with ongoing medication. The MRI scan of the brain revealed bilateral, asymmetrical FLAIR hyperintensities within the amygdala and medial temporal lobes (MTL) on both sides, as well as in the left capsuloganglionic region. Further investigations revealed presence of LGI 1 antibodies in both CSF and serum. Subsequently, administration of intravenous immunoglobulin and steroids was initiated, which demonstrated a significant enhancement in her cognitive function. This case study serves to underscore critical elements that ought to prompt the early suspicion of LGI1 encephalitis, such as hyponatremia, autonomic dysfunction, and recurrent refractory seizures. The prompt identification of this condition is correlated with an increased probability of improved clinical results and the maintenance of brain structural integrity, which is intricately connected to the commencement of immunosuppressive treatment.